Physiological, Performance, and Oxidative Stress Responses to High-Intensity Uphill and Downhill Interval Training - Theofilidis, George; Bogdanis, Gregory C.; Kaltsatou, Antonia; Poulianiti, Konstantina P.; Mitrou, Georgia I.; Rosa, Clara Suemi da Costa [UNESP]; Georgakouli, Kalliopi; Stavropoulos-Kalinoglou, Antonios; Krase, Argyro A.; Chasioti-Fourli, Fani; Syrmos, Nikolaos; Sakkas, Giorgos K.; et al. (MDPI, 2025)
Objectives: We examined how opposing running slopes can modulate interval training effects on aerobic performance and reduction–oxidation (REDOX) determinants. Methods: Fourteen physically active volunteers, assigned to either the Uphill group (UG) or the Downhill group (DG), completed 16 workouts of ten 30-s runs, at either +10% or −10% grade, with a work-to-rest ratio of 1:2 at 90% of their Maximum Aerobic Speed (MAS) over 8 weeks. Maximal oxygen uptake (VO2max), MAS, Running Economy (RE), time to exhaustion at MAS (Tmax), respiratory exchange ratio (RER), and blood lactate at rest, 5th, and 10th runs were evaluated pre-, mid-, and post-training. Also, REDOX markers [Total Antioxidant Capacity (TAC), Protein Carbonyls (PCs) were assessed in blood samples taken at rest and 3 min post-exercise of the first and last workouts. Results: VO2max was unchanged in both groups; in the DG, MAS increased (from 14.2 ± 1.7 to 15.0 ± 1.5 km/h, d = 0.43), and post-training RER significantly increased (from 1.06 ± 0.07 to 1.12 ± 0.03). In the last training session, blood lactate levels increased in the UG (from 9.30 ± 2.69 mmοl/L to 13.34 ± 4.64 mmοl/L) but remained low and unchanged in DG (<2 mmοl/L). Post-training, resting TAC decreased in both groups, and the exercise-induced rise in PC levels was attenuated. Conclusions: Despite the brief intervention, VO2max levels were maintained in both groups, with divergent changes in metabolic, REDOX, and performance indicators; uphill HIIT may serve for enhancing lactate tolerance, while downhill intermittent running may improve running economy.